Evaluation of the satisfaction of users of a service specialized in diabetes mellitus - Niciane Bandeira Pessoa Marinho; Roberto Wagner Júnior Freire de Freitas; Kenya Waléria de Siqueira Coelho Lisboa; Ana Maria Parente Garcia Alencar; Vitória de Cássia Félix Rebouças; Marta Maria Coelho Damasceno
ABSTRACT Objective: to evaluate the satisfaction of users of a service that specializes in diabetes mellitus. Method: evaluative research, with mixed approach, developed at the Integrated Center for Diabetes and Hypertension of Barbalha-CE, in the period from 2011 to 2014, with 97 users. Data concerning the characterization and satisfaction of users in relation to the dimensions of infrastructure, accessibility and the user-health team relationship were collected. Results: 77.3% were older adults, 88.7% women and 84.8%, retired. 63.9% of the users were satisfied with the service; however, dissatisfaction with the dimensions of infrastructure (offices, equipment and medicines) and accessibility (laboratory tests and medical consultations) was reported. Final considerations: most users revealed be satisfied with the service received considering the dimensions analyzed. However, studies that assess the satisfaction of users need to contemplate the participants' reports and not rely on the use of previously structured forms only.